Linking the timing of disseminated granite-hosted gold-rich deposits to paleoproterozoic felsic magmatism at alta floresta gold province, Amazon Craton, Brazil: Insights from pyrite and molybdenite Re-Os geochronology - De Assis, Rafael Rodrigues [UNESP]; Xavier, Roberto Perez; Creaser, Robert A. (Society of Economic Geologists, 2017)
The Alta Floresta gold province consists of Paleoproterozoic (2.0-1.75 Ga) plutonic-volcanic sequences that originated from successive magmatic arcs accreted to the central Amazon tectonic province in the southwestern portion of the Amazon craton. A significant number of high-grade, low-tonnage (<5 t) gold systems occur in this province along a NW-SE-striking belt, particularly in its eastern segment, close to the limits between Ventuari- Tapajós (1.95-1.80 Ga) and Rio Negro-Juruena (1.80-1.55 Ga) geochronological provinces or Tapajós-Parima (2.1-1.87 Ga) and Rondônia-Juruena (1.82-1.54 Ga) tectonic provinces. Most of these gold systems are hosted by oxidized, I-type, calc-alkaline to subalkaline, medium- to high-K, metaluminous to weakly peraluminous granitic intrusions. Among these, Pé Quente, Luizão, and X1 are the major representative deposits in the eastern segment of the Alta Floresta gold province in which gold mineralization occurs, mainly disseminated, in the host intrusions. These include biotite tonalite (1901 ± 6.8 Ma) and monzonite (1979 ± 31 Ma) for the Pé Quente, syenogranite-monzogranite (1970 ± 3 and 1964 ± 1 Ma) for the Luizão, and biotite granodiorite (1904 ± 4.6 Ma) and quartz-feldspar porphyry (1784 ± 10 Ma) for the X1 gold deposits. Within the gold-rich zones, the host granites are strongly altered to sericite-muscovite + chlorite + quartz (phyllic-like alteration) and contain abundant pyrite with variable amounts of chalcopyrite ± molybdenite ± hematite together with subordinate barite, sphalerite, galena, and Bi-Te-Ag-bearing phases. These zones are enveloped by widespread and pervasive potassic alteration with orthoclase + microcline ± hematite, which is preceded by more localized sodic alteration with albite ± quartz. The gold commonly occurs as inclusions (<180 μm) in pyrite, although pyrite-molybdenite appears in frequent association with gold at the X1 deposit. These petrographic relationships suggest that precipitation of gold and sulfides was coeval. Gold-related pyrite from the Luizão and Pé Quente and molybdenite from the X1 intrusion-hosted deposits were dated by the Re-Os method to constrain the timing of the gold metallogeny and its potential genetic link with specific felsic intrusion events in the province. The Re-Os pyrite ages for the Pé Quente deposit vary from 1792 ± 9 to 1784 ± 11 Ma, whereas those for the Luizão deposit are between 1805 ± 21.5 and 1782 ± 8.9 Ma. The X1 molybdenite yields ages of 1787 ± 7 and 1785 ± 7 Ma. These ages are markedly distinct from those of their host granites but display a close temporal association with the quartz-feldspar porphyry intrusion at the X1 deposit. Porphyries have been recognized in other gold deposits of the eastern sector of the province, but only a few have been dated and returned ages of ca. 1.80 to 1.78 Ga. These ages mark an important gold metallogenetic event in the Statherian in which the ore-forming processes are temporally connected with the felsic magmatism developed during the last stages of evolution of the Juruena magmatic arc (ca. 1.81-1.75 Ga). This felsic magmatism is represented by volcanic rocks and intrusions of the Colíder Group and epizonal granitic rocks of the Paranaíta Intrusive Suite. Despite the dominance of 1.97 and 1.87 Ga granitic intrusions as hosts to gold mineralization in the eastern sector of the Alta Floresta gold province, our Re-Os ages suggest that intrusions temporally equivalent to the Juruena felsic magmatism, particularly porphyries, may have been potential sources for fluids and metals. Thus, the Re-Os data have constrained the timing of the gold metallogeny in the Paleoproterozoic Alta Floresta gold province and have opened new perspectives for gold exploration in the province.